Body Weight Has Limited Influence on the Safety, Tolerability, Pharmacokinetics, or Pharmacodynamics of Rivaroxaban (BAY 59-7939) in Healthy Subjects - Kubitza, Dagmar; Becka, Michael; Zuehlsdorf, Michael; Mueck, Wolfgang (Journal of clinical pharmacology, 2007)
Anticoagulants are often dose adjusted, or their use restricted, in patients with extremes of body weight. Rivaroxaban (BAY 59‐7939) is a novel, oral, direct factor Xa inhibitor in clinical development. This was a randomized, single‐blind, placebo‐controlled, parallel‐group study in healthy male and female subjects to assess the effect of extreme body weight (≤50 kg and >120 kg), and gender, on the safety, tolerability, pharmacokinetics, and pharmacodynamics of rivaroxaban 10 mg, compared with subjects of normal weight (70–80 kg). Rivaroxaban was well tolerated. Cmax of rivaroxaban was unaffected in subjects >120 kg but was increased by 24% in subjects weighing ≤5 0 kg, resulting in a small (15%) increase in prolongation of prothrombin time, which was not considered clinically relevant. The area under the curve was unaffected by body weight or gender. No other clinically relevant differences were observed, suggesting that rivaroxaban is unlikely to require dose adjustment for body weight or gender.